Crescimento e morfofisiologia do dossel do capim-tanzânia com três freqüências de desfolhação e dois resíduos pós-pastejo - Cutrim Junior, José Antônio Alves (2007)
The research was carried through with the objective of evalua ting the growth and morphophysiological characteristics in canopy of Tanzania grasses under intermittent grazing with three defoliation frequencies and two post-grazing residues. The research was driven in the advanced field of the Nucleu s of Teaching and Study in Forragicultura- NEEF/DZ/CCA/UFC, located in Experi mental Farme it is Worth of Curú- FEVC/CCA/UFC, in Pentecoste/CE. The method of used grazing was it of intermittent grazing with tax of variable capacity with peri od of pastejo of four days. The split plot was it entirely randomizer in a factorial arrangemen t 3 x 2 being, three defoliation frequencies of the pasture established in f unction of the necessary time fo r the restoration of an area index to foliate that it intercepts 85; 95 a nd 97% of the photosyntheti cally active radiation (PAR) and two residues powder grazing, constitu ted of two residual IAF's, 1.0 and 1.8. Such variables were certain through the An alisador PAR/LAI in Agricultura DECAGON PAR-80 (DECAGON Devices, Inc ., Pullman, Washington-use s). The interval among pastejo went larger for PD 97% IRFA (34 days) and for IAFr 1.0 (28.2 days). The curve of evolution of IRFA came asymptot ic in relation to age of re growth of the grass, being stabilized at the level of 95% interception PA R. Already the curve of evolution of IAF was growing, even after reaching critical IAF. Ther e was effect of IRFA, of IAFr (P<0.05) and of the interaction IRFA x IAFr (P<0.15) on TAlF1/TAlF2. Para TAlF was noticed effect of IRFA and of IAFr (P<0.05), a nd smallest interception (85% IRFA) and largest IAFr (1.8) they were the ones that obtaine d larger TAlF. TAlH suffered e ffect just of IRFA (P<0.05). There was effect of IRFA and of IAFr (P<0.05) on TST, and most lingering IRFA (1.20 cm/perxdia) and IAFr 1.0 (0.96 cm/perxdia) that had largest TST. The interception of 85% (0.12 leaf/days), as well as IAFr 1.8 (0.11 l eaf/days) they obtaine d the largest values of TApF. Phylochron suffered e ffect of IRFA (P<0.05) and of the interaction IRFA x IAFr (P<0.15) with 11.05 days/leaf for 95% IRFA an d the interaction happening for 85% IRFA. There was effect just of IRFA (P<0.05) for TAF. There was e ffect of IRFA (P <0.05) on IAF. The height suffered so much effect of IRFA, as of IAFr (P<0.05). MSFT and MSFV suffered effect just of IRFA (P<0.05). MSFM suff ered effect just of the interac tion IRFA x IAFr (P<0.15), happening for 85% IRFA. There was effect of the interaction IRFA x IAFr about the relationship MV/MM (P<0.15). There was effect just of IRFA (P<0.05) on MSLV and MSCV. There was effect of IAFr (P<0.05) about the relationship Leaf/stem.